The role of apoptosis in spinal cord injury: a bibliometric analysis from 1994 to 2023 - Wang, Siqiao; Cheng, Liming (Frontiers in Cellular Neuroscience, 2024)
Background: Apoptosis after spinal cord injury (SCI) plays a pivotal role in the secondary injury mechanisms, which cause the ultimate neurologic insults. A better understanding of the molecular and cellular basis of apoptosis in SCI allows for improved glial and neuronal survival via the administrations of anti-apoptotic biomarkers. The knowledge structure, development trends, and research hotspots of apoptosis and SCI have not yet been systematically investigated. Methods: Articles and reviews on apoptosis and SCI, published from 1st January 1994 to 1st Oct 2023, were retrieved from the Web of Science™. Bibliometrix in R was used to evaluate annual publications, countries, affiliations, authors, sources, documents, key words, and hot topics. Results: A total of 3,359 publications in accordance with the criterions were obtained, which exhibited an ascending trend in annual publications. Leading countries in terms of publication numbers and active cooperation with other countries were the USA and China. Journal of Neurotrauma was the most impactive journal; Wenzhou Medical University was the most prolific affiliation; Cuzzocrea S was the most productive and influential author. “Apoptosis”, “spinal-cord-injury”, “expression”, “activation”, and “functional recovery” were the most frequent key words. Additionally, “transplantation,” “mesenchymal stemness-cells,” “therapies,” “activation,” “regeneration,” “repair,” “autophagy,” “exosomes,” “nlrp3 inflammasome,” “neuroinflammation,” and “knockdown” were the latest emerging key words, which may inform the hottest themes. Conclusions: Apoptosis after SCI may cause the ultimate neurological damages. Development of novel treatments for secondary SCI mainly depends on a better understanding of apoptosis-related mechanisms in molecular and cellular levels. Such therapeutic interventions involve the application of anti-apoptotic agents, free radical scavengers, as well as anti-inflammatory drugs, which can be targeted to inhibit core events in cellular and molecular injury cascades pathway.